Research progress in prevention and nursing of shoulder-hand syndrome in stroke patients (中风患者肩手综合征的预防与护理进展) - GUO Linyu (郭琳宇); CHEN Ying (陈迎) (中西医结合护理)
Shoulder-hand syndrome is one of the common complications after stroke. It can cause pain, swelling and other symptoms of the affected limb, and also lead to different degrees of dysfunction, which has adverse effects on the physical and mental health and quality of life of patients. This article describes the clinical manifestations and pathogenic factors of shoulder-hand syndrome, and summarizes its preventive measures and clinical nursing measures in order to provide new ideas for clinical nursing. (肩手综合征是中风后患者常见的并发症之一, 可引起患肢疼痛、肿胀等症状, 还会导致不同程度的功能障碍, 对患者的身心健康和生活质量均造成不良影响。本文对肩手综合征的临床表现与致病因素进行阐述, 对其预防措施、临床护理措施进行总结, 以期为临床护理提供新思路。)